PRODUCTION AND CHARACTERIZATION OF GREEN POLYMER COMPOSITE WITH NATURAL FILLERS - Islam, M A; Saadi, M A S R (MATTER: International Journal of Science and Technology, 2018)
Nowadays, development of environment friendly (green), high efficiency and low cost engineering materials is the main focus of researchers, where composite is at the central point. In this regard, natural fiber reinforced polymer composites have gained much attention because of their light weight, ease of fabrication, biodegradability, etc. A large amount of sand/clay mineral is also widely used as fillers for polymer composites. This paper deals with the effects of jute fiber and river based sand particle on the tensile strength and biodegradability of polyester matrix composites. At first, composites were developed and half of samples were kept under wet soil for six months to evaluate their biodegradability. Tensile tests of all samples were done by tensile testing machine. Experimental results revealed that addition of jute fiber enhances the biodegradability, but reduces the strength of the polymer, whereas, fine sand particles help regain the strength of the composite without adding any remarkable change in biodegradability.